Integrating Sleep Knowledge Into the Anesthesiology Curriculum. (14th April 2021) - Singh, Mandeep; Gali, Bhargavi; Levine, Mark; Strohl, Kingman; Auckley, Dennis
Abstract : There is common ground between the specialties of anesthesiology and sleep medicine. Traditional sleep medicine curriculum for anesthesiology trainees has revolved around the discussion of obstructive sleep apnea (OSA) and its perioperative management. However, it is time to include a broader scope of sleep medicine–related topics that overlap these specialties into the core anesthesia residency curriculum. Five main core competency domains are proposed, including SLeep physiology; Evaluation of sleep health; Evaluation for sleep disorders and clinical implications; Professional and academic roles; and WELLness (SLEEP WELL). The range of topics include not only the basics of the physiology of sleep and sleep-disordered breathing (eg, OSA and central sleep apnea) but also insomnia, sleep-related movement disorders (eg, restless legs syndrome), and disorders of daytime hypersomnolence (eg, narcolepsy) in the perioperative and chronic pain settings. Awareness of these topics is relevant to the scope of knowledge of anesthesiologists as perioperative physicians as well as to optimal sleep health and physician wellness and increase consideration among current anesthesiology trainees for the value of dual credentialing in both these specialties.